2016
DOI: 10.1371/journal.pone.0166458
|View full text |Cite
|
Sign up to set email alerts
|

TLR4/CD14 Variants-Related Serologic and Immunologic Dys-Regulations Predict Severe Sepsis in Febrile De-Compensated Cirrhotic Patients

Abstract: Genetic variants and dysfunctional monocyte had been reported to be associated with infection susceptibility in advanced cirrhotic patients. This study aims to explore genetic predictive markers and relevant immune dysfunction that contributed to severe sepsis in febrile acute de-compensated cirrhotic patents. Polymorphism analysis of candidate genes was undergone in 108 febrile acute de-compensated cirrhotic patients and 121 healthy volunteers. Various plasma inflammatory/regulatory cytokines, proportion of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The risk allele T of rs2569190 for pneumococcal disease susceptibility in our meta-analysis, is associated with high sCD14 levels in expression studies [100, 101]. Our findings correspond with other studies showing the T allele is associated with an increased occurrence of sepsis and increased serum sCD14 levels in patients with risk genotypes [102] [103]. Although the causal allele might be not the association signal due to linkage disequilibration, these studies are suggestive for a causal relationship of genetic variation in both MBL2 or CD14 and susceptibility to pneumococcal disease.…”
Section: Discussionsupporting
confidence: 90%
“…The risk allele T of rs2569190 for pneumococcal disease susceptibility in our meta-analysis, is associated with high sCD14 levels in expression studies [100, 101]. Our findings correspond with other studies showing the T allele is associated with an increased occurrence of sepsis and increased serum sCD14 levels in patients with risk genotypes [102] [103]. Although the causal allele might be not the association signal due to linkage disequilibration, these studies are suggestive for a causal relationship of genetic variation in both MBL2 or CD14 and susceptibility to pneumococcal disease.…”
Section: Discussionsupporting
confidence: 90%
“…In this context, rs2569190 G allele seems to be implicated in down-regulation of CD14 transcription and lower expression of mCD14 and circulating levels of sCD14 19 , 20 . With this in mind, previous reports suggest that the biological correlation of the CD14 rs2569190 polymorphism with the survival in patients with A-allele could be attributed to the strongest pro-inflammatory response among patients, consequence of higher CD14 expression 19 , 20 , 31 33 . This assumption is consistent with the increasingly prevailing opinion that the major problem of sepsis patients is the predominant state of immunosuppression characterized by a reduced pro-inflammatory status and increased anti-inflammatory response 16 .…”
Section: Discussionmentioning
confidence: 97%
“…Polymorphisms of pattern recognition receptors, such as nucleotide-binding oligomerisation domain containing 2 (NOD2), Toll-like receptor (TLR) 2 and 4, or nuclear dot protein 52 kDa have been associated with an increased risk of bacterial infections in some studies, but this has not been confirmed by other studies. [79][80][81][82] Sodium dismutase polymorphisms, another critical enzyme in immune defence and cell damage, were associated with decompensation and risk of bacterial infections. 83 In another study, the PNPLA3 G/G genotype was associated with a 2fold increase in the risk of decompensation.…”
Section: Genetic Predispositionmentioning
confidence: 99%